“To partake in the reality of the fulfilled will of God”: Voluntarism and participation in Bonhoeffer’s Ethics - King, Christoper (Stellenbosch Theological Journal, 2025)
This article exposits Dietrich Bonhoeffer’s account of participation as it appears in the theology of Ethics to clarify the extent to which his ontology of participation resembles or diverges from other participatory ontologies. In particular, this article argues for the centrality of the role of the will in Bonhoeffer’s concept of participation in the reality of God in Christ. His language of participation is thus an expression of his voluntarism, which is ultimately a commitment to the claim that the human will in relation to God’s reality and will is central to both justification and a Christian ethics. Because the relation between God and humanity is grounded in the event of justification, which is an encounter between wills, participation in Christ also takes the form of a relation between the human and divine will. This account is sufficient to distinguish it from alternative ontologies of participation.